1999
DOI: 10.1348/000711099159026
|View full text |Cite
|
Sign up to set email alerts
|

On fitting latent class models for binary data: The estimation of standard errors

Abstract: We investigate the uncertainty of the estimators in unrestricted latent class analysis applied to binary data. First, we use maximum likelihood theory to obtain asymptotic estimates for the standard errors of the parameters. Second, we consider models that were tted to data from two large surveys and compare the asymptotic standard errors with empirical estimates obtained using a parametric bootstrap. Third, we investigate the variability of the asymptotic standard errors via a simulation study, which gives in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 12 publications
0
13
0
Order By: Relevance
“…For this reason, we reanalyzed the data using latent class analysis to check the robustness of our conclusion that three distinct clusters of firms were extant in our sample. Latent class analysis differs from cluster analysis in that it is estimated by maximum likelihood and the number of clusters is determined by goodness‐of‐fit criteria (de Menezes, ). Bootstrapped χ 2 difference tests indicated that three clusters fit the data better than two clusters (χ 2 = 52.8, p < .001) and that four clusters did not fit the data better than three clusters (χ 2 = 19.6, ns).…”
Section: Methodsmentioning
confidence: 99%
“…For this reason, we reanalyzed the data using latent class analysis to check the robustness of our conclusion that three distinct clusters of firms were extant in our sample. Latent class analysis differs from cluster analysis in that it is estimated by maximum likelihood and the number of clusters is determined by goodness‐of‐fit criteria (de Menezes, ). Bootstrapped χ 2 difference tests indicated that three clusters fit the data better than two clusters (χ 2 = 52.8, p < .001) and that four clusters did not fit the data better than three clusters (χ 2 = 19.6, ns).…”
Section: Methodsmentioning
confidence: 99%
“…Results reported by de Menezes (1999) show that the asymptotic theory may provide a very poor approximation, even if the sample size is of the order of 1000. Nevertheless, the theoretical comparison of 2d versus 2d − 1 parameters is valid.…”
Section: Behavior Of the Log-likelihood For The 2-factor Copula Modelmentioning
confidence: 99%
“…De Menezes [5] has shown that the standard error based on the asymptotic information matrix evaluated at the MLEs can be problematic when data are sparse. In our analysis with binary test outcome, compared to the bootstrap method, Louis’s formula for adjusting information matrix based estimates of standard errors performs reasonably well when n = 122.…”
Section: Simulation Studiesmentioning
confidence: 99%